2006
DOI: 10.1159/000094959
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Pulmonary Embolism as a Sign of Acute Heparin-Induced Thrombocytopenia in Hemodialysis Patients: Safety of Resuming Heparin after Disappearance of HIT Antibodies

Abstract: Heparin-induced thrombocytopenia (HIT) is a syndrome caused by platelet-activating antibodies that recognize complexes of platelet factor 4 (PF4) and heparin. Thrombocytopenia is the most common clinical feature of HIT. HIT can be considered as a hypercoagulable state, with a high risk of thrombosis. Another feature of HIT is an acute systemic reaction that characteristically begins 5–30 min after receiving an intravenous bolus of unfractionated heparin, such as is commonly given for hemodialysis (HD). Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…However, there is increasing evidence that patients who have a history of clinical HIT do not show a typical anamnestic immune response when reexposed to heparin. 8,11,33 On the contrary, other reports 34,35 suggested that there might sometimes be a more rapid formation of heparin antibodies in the case of reexposure. But neither of these studies 34,35 established that their patients had had 2 distinct episodes of HIT.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is increasing evidence that patients who have a history of clinical HIT do not show a typical anamnestic immune response when reexposed to heparin. 8,11,33 On the contrary, other reports 34,35 suggested that there might sometimes be a more rapid formation of heparin antibodies in the case of reexposure. But neither of these studies 34,35 established that their patients had had 2 distinct episodes of HIT.…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, none of the 10 patients formed anti-PF4/ heparin antibodies, suggesting that the probability of forming repeat antibodies might be even lower than expected, given that approximately 50% of patients form at least a weak anti-PF4/heparin immune response after cardiac surgery, 2,12 and approximately 12% (median of 5 studies [range, 3% to 20% 2,[12][13][14][15] ]) develop a positive platelet activation assay. Two additional studies in hemodialysis patients found no recurrent antibodies or recurrent HIT among 8 patients with previous hemodialysis-associated HIT who, after disappearance of HIT antibodies, resumed anticoagulation either with UFH 16 or with low-molecular-weight heparin (LMWH) 17 for their long-term hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although hypertension is usually associated with ASR [29], in contrast, acute hypotension often occurs as a sign of cardiovascular collapse during dialysis. When dyspnea as the cardiorespiratory reaction in ASR is prominent, it is considered to be a pseudo-pulmonary embolism [30][31][32]. However, the signs and symptoms are very similar to those in dialyzer reactions, dialytic complications as disequilibrium syndrome, and circuit clotting during the procedure.…”
Section: Characteristics Of Acute Systemic Reaction In Dialytic Patientsmentioning
confidence: 99%